PARTISIPASI MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU DALAM MEMBUANG SAMPAH PADA TEMPATNYA DI LINGKUNGAN KAMPUS FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Regina Putri Riandes; Suyanto "; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTWaste is residual of human daily activities or natural processes in the solid form. Waste producer that can not be ignored are active community and development community. One of place that can be produced many waste in the city is University. Waste in the campus is usually from residual of student’s activities, food waste, student’s snack, grass, and plants in the campus area. As one of waste producer in the Campus area, university student must be responsible on throwing waste. The aims of this research are to know participation of medical faculty students on throwing waste in garbage. The type of this research is qualitative approach with in-depth interviews, focus group discussions, and observations by using snowballing sampling technique, there are 19 samples from Medical Faculty of Riau University students. This research showed that the students threw the waste in garbage without checked the suitable between waste type and garbage. The students threw waste in garbage because of their self and the ordinance. The obstacle that found by students on throwing waste were less awareness to keep the environtment and also caused by provision of garbage which it was not enough.Key words : Medical student, participation, waste.